Development of Visual Memory Capacity Following Early-Onset and Extended Blindness. (June 2022) - Gupta, Priti; Shah, Pragya; Gutnick, Sharon Gilad; Vogelsang, Marin; Vogelsang, Lukas; Tiwari, Kashish; Gandhi, Tapan; Ganesh, Suma; Sinha, Pawan
It is unknown whether visual memory capacity can develop if onset of pattern vision is delayed for several years following birth. We had an opportunity to address this question through our work with an unusual population of 12 congenitally blind individuals ranging in age from 8 to 22 years. After providing them with sight surgery, we longitudinally evaluated their visual memory capacity using an image-memorization task. Our findings revealed poor visual memory capacity soon after surgery but significant improvement in subsequent months. Although there may be limits to this improvement, performance 1 year after surgery was found to be comparable with that of control participants with matched visual acuity. These findings provide evidence for plasticity of visual memory mechanisms into late childhood but do not rule out vulnerability to early deprivation. Our computational simulations suggest that a potential mechanism to account for changes in memory performance may be progressive representational elaboration in image encoding.